Cancer-related fatigue: causes and current treatment options - Thong, Melissa S. Y.; van Noorden, Cornelis J. F.; Steindorf, Karen; Arndt, Volker (Current treatment options in oncology, 2020)
Cancer-related fatigue (CRF) is a problem for a significant proportion of cancer survivors during and after active cancer treatment. However, CRF is underdiagnosed and undertreated. Interventions are available for CRF although there is no gold standard. Based on current level of evidence, exercise seems to be most effective in preventing or ameliorating CRF during the active- and posttreatment phases.
Gesehen am 08.02.2021